The impact of oligofructose on stimulation of gut hormones, appetite regulation and adiposity. (8th April 2014) - Daud, Norlida M.; Ismail, Nurhafzan A.; Thomas, Elizabeth L.; Fitzpatrick, Julie A.; Bell, Jimmy D.; Swann, Jonathan R.; Costabile, Adele; Childs, Caroline E.; Pedersen, Camilla; Goldstone, Anthony P.; Frost, Gary S.
<x xml:space="preserve">Abstract</x> Objective To investigate the effect of nutrient stimulation of gut hormones by oligofructose supplementation on appetite, energy intake (EI), body weight (BW) and adiposity in overweight and obese volunteers. Methods In a parallel, single‐blind and placebo‐controlled study, 22 healthy overweight and obese volunteers were randomly allocated to receive 30 g day−1 oligofructose or cellulose for 6 weeks following a 2‐week run‐in. Subjective appetite and side effect scores, breath hydrogen, serum short chain fatty acids (SCFAs), plasma gut hormones, glucose and insulin concentrations, EI, BW and adiposity were quantified at baseline and post‐supplementation. Results Oligofructose increased breath hydrogen (P < 0.0001), late acetate concentrations (P = 0.024), tended to increase total area under the curve (tAUC)420mins peptide YY (PYY) (P = 0.056) and reduced tAUC450mins hunger (P = 0.034) and motivation to eat (P = 0.013) when compared with cellulose. However, there was no significant difference between the groups in other parameters although within group analyses showed an increase in glucagon‐like peptide 1 (GLP‐1) (P = 0.006) in the cellulose group and a decrease in EI during ad libitum meal in both groups. Conclusions Oligofructose increased plasma PYY concentrations and suppressed appetite, while cellulose increased GLP‐1 concentrations. EI decreased in both groups. However, these positive effects did not translate into changes in BW or adiposity.